PEDAGOGICAL DONTOLOGY AS A SCIENCE ON PROFESSIONAL BEHAVIOR OF A TEACHER, IN THE CONTEXT OF FORMING A PEDAGOGICAL IMAGE - Narzikulova F.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
The article considers the main idea of the role of professional behavior of a teacher in the formation of the pedagogical image. The article presents the analysis and modern concept of such definition as pedagogical and professional deontology. The aspect of professional image formation in the context of formation of high pedagogical culture is revealed. Pedagogical thinking and consciousness, as well as the creative potential of the teacher, which is a set of global cultural and historical experience, are considered.